2023
DOI: 10.3389/fchem.2023.1115440
|View full text |Cite
|
Sign up to set email alerts
|

The progress of research on the application of redox nanomaterials in disease therapy

Abstract: Redox imbalance can trigger cell dysfunction and damage and plays a vital role in the origin and progression of many diseases. Maintaining the balance between oxidants and antioxidants in vivo is a complicated and arduous task, leading to ongoing research into the construction of redox nanomaterials. Nanodrug platforms with redox characteristics can not only reduce the adverse effects of oxidative stress on tissues by removing excess oxidants from the body but also have multienzyme-like activity, which can pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 232 publications
0
3
0
Order By: Relevance
“…Depending on surface characteristics and environment, CeNPs exerts either anti-or pro-oxidative effects which regulate reactive oxygen species (ROS) levels in biological systems. CeNPs mimics ROS-related enzymes that protect normal cells at physiological pH range from oxidative stress and induce ROS production in the slightly acidic tumor microenvironment to trigger cancer cell death [51,52]. The results obtained, indicated that SiNPs@DOX@CeNPs provided high cytotoxicity to cancer cells while having protective effect on normal cells.…”
Section: Cytotoxicity Study Of Sinps@dox@cenpsmentioning
confidence: 93%
“…Depending on surface characteristics and environment, CeNPs exerts either anti-or pro-oxidative effects which regulate reactive oxygen species (ROS) levels in biological systems. CeNPs mimics ROS-related enzymes that protect normal cells at physiological pH range from oxidative stress and induce ROS production in the slightly acidic tumor microenvironment to trigger cancer cell death [51,52]. The results obtained, indicated that SiNPs@DOX@CeNPs provided high cytotoxicity to cancer cells while having protective effect on normal cells.…”
Section: Cytotoxicity Study Of Sinps@dox@cenpsmentioning
confidence: 93%
“…Micelles often have limited drug loading capacity compared to MSNs, potentially leading to suboptimal therapeutic doses. The release of the photosensitizer from micelles may not be as controlled as in MSNs, which can impact the desired drug release kinetics [ 141 ]. Lipid-based nanoparticles, such as liposomes and lipid nanocarriers, offer excellent biocompatibility, controlled drug release, and the ability to encapsulate both hydrophilic and hydrophobic photosensitizers.…”
Section: Photodynamic Therapymentioning
confidence: 99%
“…Therefore, the concept of “redox medicine” has gained increasing attention as a promising and powerful approach to finely regulate both eustress and distress conditions, i.e. , to target both physiological and pathophysiological conditions. , Not surprisingly, the watershed between the two has been first identified in intracellular ROS concentration. , Although redox materials are used for the prevention and treatment of various diseases in the preclinical stage, translating therapeutic redox materials to the clinic is still evolving. , …”
Section: Introductionmentioning
confidence: 99%
“…6,7 Although redox materials are used for the prevention and treatment of various diseases in the preclinical stage, translating therapeutic redox materials to the clinic is still evolving. 8,9 ROS can be produced endogenously, from an incomplete reduction of oxygen and the enzyme nicotinamide adenine dinucleotide phosphate oxidase in the plasma membrane, or through exogenous stimuli like UV light, ionizing radiation, or xenobiotics. 10 While endogenous biochemical approaches are effective to target cellular redox signaling processes, they are irreversible and present limited spatiotemporal resolution.…”
Section: Introductionmentioning
confidence: 99%